Dexmedetomidine post-conditioning protects blood-brain barrier integrity by modulating microglia/macrophage polarization via inhibiting NF-κB signaling pathway in intracerebral hemorrhage - Guo, Hao; Zhang, Weiwei; Wang, Zhi; Li, Zhishan; Zhou, Jing; Yang, Zhaoyu (Frontiers in Molecular Neuroscience, 2022)
Intracerebral hemorrhage (ICH) is one of the most devastating forms of stroke. Dexmedetomidine (DEX) has shown certain neuroprotective roles in ICH. Nevertheless, the details concerning the underlying molecular mechanism of DEX’s protective effects still need further elucidation. Herein, a model of ICH was established. The rats were randomly divided into the Sham group, the ICH group, and the ICH+DEX group. Neurological outcomes, neuronal injury and apoptosis were evaluated. Brain water content, Evans blue extravasation, and the expression of tight junction-associated proteins were also detected to assess the blood-brain barrier (BBB) integrity. Subsequently, the microglia/macrophage polarization state and inflammatory cytokine levels were observed. To further explore the underlying mechanism, NF-κB signaling pathway-associated proteins were detected. The results showed that DEX exerted neuroprotective effects against ICH-induced neurological deficits. DEX significantly increased the numbers of the surviving neurons, ameliorated neuronal cell loss and apoptosis in ICH. The rats that received the DEX displayed a lower level of brain water content and EB extravasation, moreover, ZO-1, occluding and claudin-5 were markedly increased by DEX. Additionally, DEX facilitated M2 microglia/macrophage polarization, the M1-associated markers were reduced by DEX, while the M2-associated identification significantly increased. We found that DEX dramatically diminished pro-inflammatory cytokines expression, simultaneously promoting anti-inflammatory cytokines expression. DEX inhibited nuclear translocation of NF-κB in ICH rats. Our data suggest that DEX post-conditioning protects BBB integrity by modulating microglia/macrophage polarization via inhibiting the NF‑кB signaling pathway in ICH.